The insulin-like growth factor system is modulated by exercise in breast cancer survivors: a systematic review and metaanalysis (2016)
Background: Insulin-like growth factors (IGFs) play a crucial role in controlling cancer cell proliferation, differentiation and apoptosis. Exercise has been postulated as an effective intervention in improving cancer-related outcomes and survival, although its effects on IGF are not well understood. This meta-analysis aimed to determine the effects of exercise in modulating IGFs system in breast cancer survivors. Methods: Databases of PuMed, EMBASE, Cochrane Central Register of Controlled Trials, EMBASE, ClinicalTrials.gov, SPORTDiscus, LILACS and Scopus were systematically searched up to November 2014. Effect estimates were calculated through a random-effects model of meta-analysis according to the DerSimonian and Laird method. Heterogeneity was evaluated with the I 2 test. Risk of bias and methodological quality were evaluated using the PEDro score. Results: Five randomized controlled trials (n=235) were included. Most women were post-menopausal. High-quality and low risk of bias were found (mean PEDro score=6.2±1). Exercise resulted in significant improvements on IGF-I, IGF-II, IGFBP-I, IGFBP-3, Insulin and Insulin resistance (P<0.05). Non-significant differences were found for Glucose. Aerobic exercise improved IGF-I, IGFBP-3 and Insulin. No evidence of publication bias was detected by Eggeŕs test (p=0.12). Conclusions: Exercise improved IGFs in breast cancer survivors. These findings provide novel insight regarding the molecular effects of exercise on tumoral microenvironment, apoptosis and survival in breast cancer survivors. © 2016 The Author(s).